Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

Matt71

  • 4 years ago

Make x the subject of the formula

  • This Question is Closed
  1. Matt71
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

  2. S
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    y = sqrt((5x + 3)/(x-5)) y^2 = (5x+3)/(x-5) (y^2) * (x-5) = 5x + 3 x*(y^2) - 5*(y^2) = 5x + 3 x*(y^2) - 5x = 3 + 5*(y^2) x*((y^2) - 5) = 3 + 5*(y^2) x = (3 + 5*(y^2)) / ((y^2) - 5)

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy